Physical Exercise Increases Nasal Patency in Asthmatic and Atopic Preschool Children. Issue 6 (November 2013) - Haavisto, Lotta E.; Lukkarinen, Minna; Lukkarinen, Heikki; Jartti, Tuomas; Papadopoulos, Nikolaos G.; Sipilä, Jukka I.
Background: Physical exercise causes a decrease in nasal mucosal congestion and hence an increase in nasal patency. This nasal response has been studied only in adults. A correlation between nasal obstruction and asthma or allergic rhinitis has been previously found. This study evaluates the influences of atopy and asthma on nasal patency and the changes in nasal patency induced by physical exercise in preschool children. Methods: An 8-minute exercise challenge test was conducted in 31 children aged between 4.1 and 6.4 years: 13 children had asthma, 17 were atopic, and 13 had neither asthma nor atopy. Nasal patency was measured with acoustic rhinometry at baseline and 10 minutes after the exercise. Results: At baseline, the total acoustic values were 17–25% larger in nonasthmatic children than in asthmatic children. Accordingly, the acoustic values in nonatopic children were 16–35% larger than in atopic children. After physical exercise, there was an overall increase in mean total nasal volume from 2.973 (SD = 0.647) to 3.405 cm 3 (SD = 0.705), indicating an improvement of 15% in nasal volume (p = 0.025). The increase in nasal patency was similar in asthmatic and nonasthmatic children, as well as in atopic and nonatopic children. Conclusion: A significant increase in total nasal volume after physical exercise was found in all preschool children. The minimal cross-sectional areas remained smaller in asthmatic and atopic children after exercise, indicating partly irreversible nasal mucosal congestion in these children.